2017
DOI: 10.1007/s00384-017-2932-3
|View full text |Cite
|
Sign up to set email alerts
|

Staging with computed tomography of patients with colon cancer

Abstract: There is basis for improvement of CT-based preoperative staging of patients with colorectal cancer. Supplementary modalities may be needed for correct staging of patients preoperatively, especially in relation to stratification of patients into neoadjuvant treatments or tailored therapy in patients with early cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 25 publications
5
25
0
Order By: Relevance
“…This In concordance with a systematic review [20] and a Danish single-centre study [21] we found that it remains a challenge to correctly identify patients with locally advanced disease. In our study only 61% of patients with locally advanced disease and 85% without locally advanced disease were correctly identified on MDCT.…”
Section: Discussion and Con Clus Ionssupporting
confidence: 89%
“…This In concordance with a systematic review [20] and a Danish single-centre study [21] we found that it remains a challenge to correctly identify patients with locally advanced disease. In our study only 61% of patients with locally advanced disease and 85% without locally advanced disease were correctly identified on MDCT.…”
Section: Discussion and Con Clus Ionssupporting
confidence: 89%
“…The selected papers are summarized in Table 3 82‐93 . For T staging (Table 3A), Chen et al revealed that dual‐energy CT showed a high accuracy, with a sensitivity of 90% and specificity of 97% 83 .…”
Section: Resultsmentioning
confidence: 99%
“…For lymph node staging (Table 3B), the sensitivity was found to range from 44% to 73%, and the specificity ranged from 41% to 84%. [84][85][86][87][88][89][90] The accuracies of these studies were around 50%-60%. PET showed a relatively high specificity of 84%, but a sensitivity of only 44%.…”
Section: Lymph Node Stagingmentioning
confidence: 99%
“…For adrenal incidentaloma, non-enhanced CT and HU of ROI can be used to discriminate benign from malignant lesions (14,16). In colon cancer, ceCT analysis in the portal venous phase is the current standard method for initial disease staging (30). Ravanelli et al used texture analysis of ceCTs for response prediction in patients treated with bevacizumab, with a remarkable correlation of OS and texture analysis in this subgroup of patients (31).…”
Section: Discussionmentioning
confidence: 99%